PENGARUH PERMODALAN, KUALITAS AKTIVA, LIKUIDITAS, DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS PADA PT BANK SYARIAH MANDIRI DAN PT BANK BRI SYARIAH - MARLINA WIDIYANTI; TAUFIK .; GITA LYANI PRATIWI (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This study aimed to determine the effect of capital , asset quality , liquidity and operational efficiency on profitability in Islamic banks period of 2009 - 2013. The object of this study is the Bank Syariah Mandiri and Bank BRI Syariah. The variables used in this study is CAR , NPF , FDR , ROA and ROA. Data analysis method used is Multiple Linear Regression. The empirical results showed that partially the CAR and NPF had no significant effect on ROA. FDR had positive and significant impact on ROA. BOPO had significant negative effect on ROA. Simultaneously, CAR, NPF, FDR and BOPO had positive and significant impact on ROA with the coefficient of determination R Square ( R2) of 92,3 % on Bank Syariah Mandiri and Bank BRI Syariah. The results of this study have implications for Islamic banks as a suggestion to improve the financial performance.